Comparison of Different Strategies for Prevention of Catheter-Related Bladder Discomfort: A Randomized Controlled Trial - Fatma Ozkan Sipahioglu; Filiz Karaca Akaslan; Ozge Yamankilic Mumcu; Reyhan Polat; Fatih Sandikci; Asli Donmez (Haseki Tıp Bülteni, 2022)

(untitled)
Aim:Catheter-related bladder discomfort (CRBD) is characterized by pain and a burning sensation in the suprapubic region caused by stimulation of type 3 muscarinic (M3) receptors. The aim of this study was to compare the effects of tramadol and dexmedetomidine on CRBD, which have inhibitory effects on the M3 receptor.Methods:A total of 135 male patients with ASA I-II, aged between 18 and 70 years and scheduled to undergo elective retrograde intrarenal surgery between March and July 2020, were included in the study. Patients were randomized into three groups: tramadol (group T), dexmedetomidine (group D), and control (group C). Patients were evaluated for the incidence and severity of CRBD and postoperative pain at the postoperative 0th (t0), 1st (t1), 3rd (t2), and 6th (t3) hours.Results:The incidence and severity of CRBD were lower in group D at t1 than in the other groups (p<0.05). The incidence and severity of CRBD were similar between groups T and D, and they were significantly lower than those in group C at t2 and t3 (p<0.01). Postoperative pain levels were significantly lower in groups T and D than in group C at t0 and t1 (p<0.01). Postoperative recovery time was significantly longer in group D (p<0.01).Conclusion:Both dexmedetomidine and tramadol are effective in preventing CRBD and in postoperative analgesia. Dexmedetomidine is more potent than tramadol in the early period; however, it may delay post-anesthesia recovery time.